The Relationship Between Urinary Stone Disease and Nutrition Type in Infants - Latt, Kyaw Zin; Turkmenoglu, Yelda; Kacar, Alper; Irdem, Ahmet; Dursun, Hasan (International Journal of Child Health and Nutrition, 2022)
The relationship between urinary stone disease and nutrition in infants is not well known. This study investigates the relationship between breast milk, formula and supplementary foods, vitamin D usage, and family stone history with urinary system stones in children aged 3-24 months. The study included 100 infants aged 3-24 months of age with urinary tract stones and 40 healthy infants with similar age and gender as the control group. Sixty of the patients were boys, and 40 were girls; the control group consisted of 26 boys and 16 girls. There was no significant difference in only breastfeeding, breastfeeding plus formula, and formula feeding in the patients and controls. Positive family history of urolithiasis was significantly higher in the patients compared to the controls (p=0.04). While breastfeeding duration time was negatively correlated with spot urine calcium to creatinine ratio in children exclusively breastfed infants. No direct effect of nutrition type and vitamin D usage on stone formation was found in infants. It has been shown that stone formation in this age group is associated with a family history of stones. In this study, the duration of breastfeeding is negatively correlated with the spot urinary calcium to creatinine ratio.